A comparative study of head-elevated positions at 25° versus 45° for intubation in obese patients posted for elective surgery under general anesthesia - Koel Mitra; Fayeza Nasrin; Subhrangsu Chatterjee; Pratibha Bhunia (Asian Journal of Medical Sciences, 2024)
Background: Obese patients generally present with an increased risk of difficult intubation. The head-elevated position has been shown to improve laryngeal view, reduce airway complications, and prolong safe apnea time during intubation as compared to the sniffing position. Aims and Objectives: The aim of this study is to compare the head-elevated positions at 25° versus 45° for intubation in obese patients, in terms of ease of intubation assessed by first-attempt intubation success rate and laryngeal exposure using Cormack–Lehane grading and to assess intubation time, use of intubation aides, changes in hemodynamic parameters, and hypoxia. Materials and Methods: In this randomized controlled trial, 100 consenting patients undergoing elective surgery requiring general anesthesia were selected who fulfilled the eligibility criteria and assigned to either of the two groups by block randomization: Group A – 25° or Group B – 45° head-elevated positions for intubation in a tertiary care hospital (February 2021–July 2022). Results: The 45° head-elevated position was found to provide a better laryngeal exposure, the mean time to intubate was lesser and the first attempt success rate was also higher. Further, 45° head-elevated position is better chosen as per anesthesiologist comfort, using Likert scale grading. Conclusion: This study concluded that 45° head-elevated position provides better ease of intubation in obese patients as compared to 25° head-elevation.